Celery Electronics. (2020) - Morris, Rhiannon; Warren, Holly; in het Panhuis, Marc
ABSTRACT: Plants produce energy in a sustainable way, they are very effective in converting light energy into a useable form. Utilising certain parts of plants in technology could become an efficient way to enhance energy production and improve sustainability. Integrating plants with technology would offer a 'green' way of producing elements for electronic circuits and reduce heavy metal waste. In this paper, we demonstrate that conducting polymers can be incorporated into living system such as celery. Electrical impedance analysis was used to establish the conductivity of celery with a conducting polymer (PEDOT:PSS) into its vascular system. It was demonstrated that electronic celery exhibited conductivity values of up to 0.55 ± 0.03 S/cm. This conductivity value was sufficient to demonstrate the potential of celery electronics where celery stalks are used as electrodes in simple circuits.